PENGEMBANGAN MEDIA PEMBELAJARAN MAHÂRAH AL-KALÂM BERBASIS MEDIA SOSIAL MENGGUNAKAN APLIKASI TIKTOK - Zubaidi, Ahmad; Junanah, Junanah; Shodiq, M. Ja'far (Arabi : Journal of Arabic Studies, 2021)
This study aims to develop social media-based Mahārah al-kalām learning media using the TikTok application and to test the feasibility of these learning media. In the development of this learning media, the researcher used the ADDIE (analysis, design, development, implementation, and evaluation) development type with 42 students as respondents in the Arabic language course at the Islamic Education Study Program of the Universitas Islam Indonesia with the data collection technique in the form of a questionnaire which included components, material, display, and operation/use. From the feasibility test of learning media by media experts, a percentage of 85.7% was obtained with the very feasible category, the material expert test obtained a percentage of 92.8% with a very feasible category. Then the learning media was tested extensively (in the field) to 42 students by getting a percentage of 82.12% in the very feasible category. The average of the results of the expert tests and trials mentioned above, the percentage results are 86.9%, which means that the social media-based mahārah al-kalām (speaking skill) learning media using the TikTok application is very feasible to use.